Geodiversity Research at the Crossroads: Two Sides of the Same Coin - Ibáñez, Juan José; Brevik, Eric C. (Spanish journal of soil science, 2022)
Geodiversity research is a growing industry. However, in contrast to diversity studies in other branches of natural sciences, geodiversity specialists have only paid attention to one side of the coin. They focused on the conservation of geological heritage (geoconservation) and its role/use for economic development through geotourism. Most geodiversity experts forgot the more strictly scientific side of the coin such as the use of standard techniques to inventory georesources and analyze their spatial patterns. Furthermore, the lack of a consensual definition with universal classifications and standards to carryout inventories inhibits progress in the inventory and quantification of planetary geodiversity. Even though most definitions of geodiversity include soil resources, pedodiversity is generally ignored in geodiversity research and publications. On the other hand, pedodiversity studies tended to follow the path previously created by biodiversity experts over a period of decades, although they have not convinced policymakers to approve strategies to preserve global soil resources (parks, pedosites, reserves, etc.). Biodiversity studies paid attention to the role of diversity in the structure and function of biocenosis, ecosystems, and biomes, with preservation being placed in the hands of experts in conservation biology. The structure and dynamics of all the Earth surface systems could be analyzed using the standard mathematical tools developed for biodiversity studies and that have been applied with success in pedodiversity analyses. In fact, most of the patterns detected in biodiversity also appear in pedodiversity. According to the canons of the philosophy of science, geodiversity has not reached a paradigm shift, despite the claims of some geodiversity experts. Thus, geodiversity research is at a crossroads as it seeks to reach a genuine paradigm shift.